Adverse pregnancy and neonatal outcomes associated with Neisseria gonorrhoeae: systematic review and meta-analysis - Vallely, Lisa M; Egli-Gany, Dianne; Wand, Handan; Pomat, William S; Homer, Caroline S E; Guy, Rebecca; Silver, Bronwyn; Rumbold, Alice R; Kaldor, John M; Vallely, Andrew J; Low, Nicola (Sexually transmitted infections, 2021)
ObjectiveTo examine associations between Neisseria gonorrhoeae (NG) infection during pregnancy and the risk of preterm birth, spontaneous abortion, premature rupture of membranes, perinatal mortality, low birth weight and ophthalmia neonatorum.Data sourcesWe searched Medline, EMBASE, the Cochrane Library and Cumulative Index to Nursing and Allied Health Literature for studies published between 1948 and 14 January 2020.MethodsStudies were included if they reported testing for NG during pregnancy and compared pregnancy, perinatal and/or neonatal outcomes between women with and without NG. Two reviewers independently assessed papers for inclusion and extracted data. Risk of bias was assessed using established checklists for each study design. Summary ORs with 95% CIs were generated using random effects models for both crude and, where available, adjusted associations.ResultsWe identified 2593 records and included 30 in meta-analyses. Women with NG were more likely to experience preterm birth (OR 1.55, 95% CI 1.21 to 1.99, n=18 studies); premature rupture of membranes (OR 1.41, 95% CI 1.02 to 1.92, n=9); perinatal mortality (OR 2.16, 95% CI 1.35 to 3.46, n=9); low birth weight (OR 1.66, 95% CI 1.12 to 2.48, n=8) and ophthalmia neonatorum (OR 4.21, 95% CI 1.36 to 13.04, n=6). Summary adjusted ORs were, for preterm birth 1.90 (95% CI 1.14 to 3.19, n=5) and for low birth weight 1.48 (95% CI 0.79 to 2.77, n=4). In studies with a multivariable analysis, age was the variable most commonly adjusted for. NG was more strongly associated with preterm birth in low-income and middle-income countries (OR 2.21, 95% CI 1.40 to 3.48, n=7) than in high-income countries (OR 1.38, 95% CI 1.04 to 1.83, n=11).ConclusionsNG is associated with a number of adverse pregnancy and newborn outcomes. Further research should be done to determine the role of NG in different perinatal mortality outcomes because interventions that reduce mortality will have the greatest impact on reducing the burden of disease in low-income and middle-income countries.PROSPERO registration numberCRD42016050962.